Selection and validation of reference genes for gene expression studies by reverse transcription quantitative PCR in Xanthomonas citri subsp citri during infection of Citrus sinensis - Jacob, Tiago R. [UNESP]; Laia, Marcelo L. [UNESP]; Ferro, Jesus A. [UNESP]; Ferro, Maria I. T. [UNESP] (Springer, 2011)
Xanthomonas citri subsp. citri (Xcc) causes citrus canker, a worldwide disease found mainly in sweet oranges (Citrus sinensis (L.) Osbeck). The expression of nine candidate internal reference genes was analyzed in Xcc grown alone and during C. sinensis infection to identify genes most suitable for comparative expression studies in Xcc using reverse transcription quantitative PCR (qRT-PCR). The stability of these genes was determined using the programs geNorm, NormFinder and BestKeeper. The genes most suitable for data normalization during C. sinensis infection were atpD, rpoB, gyrA and gyrB. The use of at least three reference genes is essential for accurate data normalization in Xcc.
Keywords: Gene expression; qRT-PCR; Reference genes; Xanthomonas citri subsp. citri